Species-based indicators to assess habitat degradation: Comparing the conceptual, methodological, and ecological relationships between hemeroby and naturalness values. (March 2022) - Erdős, László; Bede-Fazekas, Ákos; Bátori, Zoltán; Berg, Christian; Kröel-Dulay, György; Magnes, Martin; Sengl, Philipp; Tölgyesi, Csaba; Török, Péter; Zinnen, Jack
Highlights: Hemeroby and naturalness values are used to reflect human impacts to vegetation. Hemeroby values are descriptive to sites whereas naturalness values appraise them. Negative correlation of hemeroby and naturalness may change along their gradients. Indicators have contrasting resolution near the ends of the degradation continuum. Both indicator values were inversely and weakly related to leaf traits. Abstract: Naturalness and hemeroby indicator values are specialized species-based indicators used in Continental Europe that reflect plant species' affinity to degraded habitats. Despite their potential utility for basic and applied science, their similarities have gone unnoticed, and they have yet to be studied together. Here, we combine literature review and novel data analyses to ask 1) How are the naturalness and hemeroby indicator systems related, and 2) Do naturalness and hemeroby indicator values reflect similar functional patterns? To address these questions, we first reviewed the conceptual and methodological differences underlying naturalness and hemeroby values. We then directly compared the indicator values, including splitting species by origin. Next, to determine if the values capture similar ecological patterns, we related the indicator values to leaf traits, specifically leaf area, dry matter content, and specific leaf area. The main conceptual difference we identified was the differing reference states of the systems: naturalness values are value-laden and emphasize a lack of human influence, whereas hemeroby values are evaluative and apply the potential natural vegetation concept. Naturalness and hemeroby indicators have contrasting resolutions on opposite ends of the naturalness/degradation continuum, with naturalness placing greater emphasis on lightly impacted areas, whereas hemeroby divides degraded contexts more finely. Overall, naturalness and hemeroby values were inversely related. Naturalness and hemeroby values were strongly (rho < -0.6) correlated in direct comparisons. These correlations were curvilinear due to the scoring differences for non-native species: the systems had contrasting score variances (i.e., resolution) between non-native and native species. Leaf traits were generally "mirror images" between the systems; hemeroby was negatively associated with dry matter content and positively associated with specific leaf area, and vice versa for naturalness.. However, these relationships were weak (R 2 < 0.05). The weakness of these patterns implies that species' degradation tolerance may not be generalizable by simple leaf traits. Our work showed that hemeroby and naturalness are inverse, bilaterally consistent indicator systems. These indicator values, or improved versions of them, could be better utilized in the future for applied management and conservation.